Active Replication Checkpoint Drives Genome Instability in Fission Yeast mcm4 Mutant - Kim, Seong Min (Mol Cell Biol, 2020)
Upon replication fork arrest, the replication checkpoint kinase Cds1 is stimulated to preserve genome integrity. Robust activation of Cds1 in response to hydroxyurea prevents the endonuclease Mus81 from cleaving the stalled replication fork inappropriately. However, we find that the response is different in temperature-sensitive mcm4 mutants, affecting a subunit of the MCM replicative helicase. We show that Cds1 inhibition of Mus81 promotes genomic instability and allows mcm4-dg cells to evade cell cycle arrest. Cds1 regulation of Mus81 activity also contributes to the formation of the replication stress-induced DNA damage markers replication protein A (RPA) and Ku. These results identify a surprising role for Cds1 in driving DNA damage and disrupted chromosomal segregation under certain conditions of replication stress.